2019
DOI: 10.4236/ce.2019.1012210
|View full text |Cite
|
Sign up to set email alerts
|

Student Teams-Achievement Divisions (STAD) in Enhancing Speaking Performance among English as Second Language (ESL) Learners: A Critical Review

Abstract: In this review, the authors critically examined the potential of Student Teams-Achievement Divisions (STAD) in enhancing student's speaking performance among English as Second Language (ESL) learners. Specifically, the cooperative language learning concept that emerged in the 2000s, including procedures of implementing STAD and teaching speaking through STAD, were discussed. The authors examined conceptualizations of this model as well as related research. This review aimed to improve our understanding of STAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…It showed 122 (92.4%) respondents who communicated in English when using social media. This was parallel to a finding that participants' willingness to share in English (WTC) was more significant of using social media than their WTC during class time (Chotipaktanasook & Reinders, 2016;Ibrahim & Adnan, 2020). Another finding from Figure 11 concluded that 110 (83.3%) respondents approved using social media to speak to native speakers of English all around the world.…”
Section: Discussionsupporting
confidence: 52%
“…It showed 122 (92.4%) respondents who communicated in English when using social media. This was parallel to a finding that participants' willingness to share in English (WTC) was more significant of using social media than their WTC during class time (Chotipaktanasook & Reinders, 2016;Ibrahim & Adnan, 2020). Another finding from Figure 11 concluded that 110 (83.3%) respondents approved using social media to speak to native speakers of English all around the world.…”
Section: Discussionsupporting
confidence: 52%
“…The STAD-type cooperative was developed by Robert Slavin and colleagues from Johns Hopkin University, US (Lubis, 2020;Tiantong & Teemuangsai, 2013). STAD cooperative is the division of small groups based on achievement by emphasizing to practice and learn information (Barus et al, 2020;Ibrahim & Adnan, 2019). The basic idea of the STAD Cooperative is how to motivate students in groups so that they can encourage and help each other in mastering the material presented, and foster an awareness that learning is important, meaningful, and fun (Esminarto et al, 2016).…”
Section: Forms Of Integration In Learningmentioning
confidence: 99%
“…Instead, it will produce a passive and dependent learner, implying that students should depend on the teachers for information, drill, and practice activities, as well as learn only for examination purposes (Blachowicz & Ogle, 2017). Some improvements are necessary to transform passive and traditional learning activities into an active and engaging learning experience to produce holistic students, not only in language learning and acquisition (Ibrahim & Adnan, 2020). Thus, providing ample opportunities and a conducive learning environment in Malaysia secondary school for students to take autonomous roles in their learning could be done by having collaboration or individual works by themselves, with some guidelines and instructions provided by the instructor or teachers.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Although the importance of the English language is generally acknowledged, most Malaysian students show a lack of effort to learn English (Ibrahim & Adnan, 2020). A case study done by Razali (2017) recognized that the poor performers recognized the importance of English for instrumental purposes and took a positive view of its use, standard, and status but did not demonstrate positive attitudes towards language learning.…”
Section: Attitudes and Motivation In Learning English As Second Languagementioning
confidence: 99%
See 1 more Smart Citation